Thymbra capitata essential oil as potential therapeutic agent against Gardnerella vaginalis biofilm-related infections. (April 2017) - Machado, Daniela; Gaspar, Carlos; Palmeira-de-Oliveira, Ana; Cavaleiro, Carlos; Salgueiro, Lígia; Martinez-de-Oliveira, José; Cerca, Nuno
Aim: To evaluate the antibacterial activity of Thymbra capitata essential oil and its main compound, carvacrol, against Gardnerella vaginalis grown planktonically and as biofilms, and its effect of vaginal lactobacilli.Materials & methods: Minimal inhibitory concentration, minimal lethal concentration determination and flow cytometry analysis were used to assess the antibacterial effect against planktonic cells. Antibiofilm activity was measured through quantification of biomass and visualization of biofilm structure by confocal laser scanning microscopy.Results: T. capitata essential oil and carvacrol exhibited a potent antibacterial activity against G. vaginalis cells. Antibiofilm activity was more evident with the essential oil than carvacrol. Furthermore, vaginal lactobacilli were significantly more tolerant to the essential oil.Conclusion: T. capitata essential oil stands up as a promising therapeutic agent against G. vaginalis biofilm-related infections.